Kesantunan Bertindak Tutur Ekspresif Anak Didik Dalam Menyatakan Terima Kasih Kepada Guru - Pratiwi, Laras; , Prof. Dr. Abdul Ngalim, M.M, M.Hum (2017)
Modesty is an important thing in communicating. But it must be realized that etiquette, courtesy, and morals should be considered and followed. In the context of learning, decency and cooperation principles are needed. Viewed today, that only some people who understand about politeness let alone conversations students to teachers. This study covers 2 objectives. (1) Principles of cooperation students' expressive speech acting in stating thanks to teachers. (2) Strategy of positive politeness and negative politeness students' expressive speech acting in stating thanks to teachers. Data collection techniques used the DCT model. Data analysis techniques used data reduction, data analysis, and conclusion. Data were analyzed using the principles of cooperation by Grice and politeness strategies by Brown and Levinson. The results of this research were 2 things. (1) Principle of cooperation were found 16 speeches, (a) quantity maxim 4 findings, (b) quality maxim 5 findings, (c) relevance maxim 3 findings, (d) implementation maxim 4 findings. (2) There are 8 sub-sections of a positive and negative politeness strategy by Brown and Levinson. Positive politeness (a) expressing with regard of the preferences, desires, and needs of the hearer, (b) Expressing with exaggeration of attention, approval and sympathy to the listener; (c) expresive by means of an offer or promise, (d) expressing by showing self deference, (e) expressing by giving gifts (goods, sympathy of attention, cooperation) to the listener. While negative politeness (a) expressing things by being pessimistic and cautious, (b) expressing by using apology.